Leadership and Employee Performance in Digital Transformation: A Systematic Review (2020–2025) - Syupriadin Syupriadin; Winda Dewi Listyasari; Linda Ika Mayasari; Kamaludin Kamaludin (Research, Training and Philanthropy Institution Natural Aceh, 2026)
This study investigates how research on Leadership and employee performance has evolved within the digital transformation landscape through a Systematic Literature Review (SLR) of publications from 2020 to 2025. The literature search was conducted in Scopus and Google Scholar using the Publish or Perish tool, with search terms including “Leadership,